Innovation and Education: Is there a 'Nerd Effect'? - Stefan Goldbach (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
Policy makers are interested in fostering economic growth and employment. Therefore, it is important to know how to boost innovation in an effective way. This paper investigates whether entrepreneurs with technical education are more innovative in high-tech industries than economists. The main contribution to the literature is in using the type of education as main explanatory variable for innovation. To analyze this question, the KfW/ZEW Start-Up Panel between 2005 and 2007 is used. Two independent OLS regressions are conducted for entrepreneurs with university degree and practical education. The results suggest that education matters for individuals with a university degree in high-tech industries but not for people with practical education. Having an economics degree is correlated with higher innovativeness. Therefore, for the underlying sample we do not find a nerd effect .
Keywords: A20; L26; I21; 330